Social Impact and Actions of Sam Ratulangi University Batak Students on Using the TikTok Application: A Study of Social Media Culture - Rahel Rahel; Shirley Y.V.I. Goni; Femmy C.M. Tasik (Journal La Bisecoman, 2024)
The development of information technology has had an impact on people's lives, including in terms of culture. Tikto is an application developed through the use of information technology. Tiktok, which is social media, is used by all people, including students. This research was conducted to examine the Social Media Culture of the Tiktok Application among Batak Students at Sam Ratulangi University, Manado, North Sulawesi Province. Qualitative design was used in this research. Research findings on the use of the TikTok application among Batak students at Sam Ratulangi University are actions that have become ingrained in their social life. The TikTok application has a positive and negative impact on the lives of Batak students at Sam Ratulangi University where their concentration is divided with other activities. However, overall, it does not affect the learning achievement of Batak students at Sam Ratulangi University, especially the informants. Tiktok becomes a unifier in their social life. The negative impact of using the Tiktok application is that you often lose track of time, become addicted, don't pay attention to your health and many more, use it in the wrong way or have crossed the line so that negative videos appear.